Analisis Kebijakan Publik dalamTransformasi Layanan Transportasi Massal - Niapele, Sarifa; Rahajaan, Jakobus Anakletus (KAMBOTI: Jurnal Sosial dan Humaniora, 2024)
This study analyzes public policy in the transformation of mass transportation services, using a multidisciplinary approach that integrates public policy studies and normative law studies. Employing qualitative research with a document (literature) study approach, the study highlights the inevitable shift from conventional to application-based transportation services, which led to the formulation of public policies regulating special rental transportation (ASK), commonly known as online transportation. However, the implementation of the ASK policy has sparked controversy, with some groups claiming that the transformation exacerbates social disparities by reducing their income. The study reveals that different types of public transportation, such as Angkot and ASK, operate under distinct regulations, objectives, service methods, and market segments. The study recommends that the government thoroughly investigate the underlying causes of competition among mass transportation service providers, including factors beyond the rise of ASK, and evaluate existing public policies in the sector. Additionally, collaboration with service providers should be encouraged to foster creativity and innovation, while addressing the factors contributing to the decline of public transportation usage. These efforts aim to promote fairness among providers through humane methods that align with the principles of legal justice.